Allyson Jule: Speaking up: Understanding Language and Gender. (Czech Journal of International Relations, 2018)
From slut-shaming to the allegedly shrill voices of female politicians, from vocal fry to online misogyny, the language women use (and the language used about them) is as controversial as it has ever been. Our language use and our gender have an enormous impact on the way we understand ourselves and the world around us, and the way we are treated by society. Using the latest academic research, Allyson Jule tackles some of the most pressing issues facing feminism today, including how language use and related ideas about gender play out in the home, workplace and online. It turns out that many popular ideas about gender and language are more complicated than they first appear. This book will change the way you think about language, and give you the tools to challenge the world around you.